New Insights and Current Approaches in Cardiac Hypertrophy Cell Culture, Tissue Engineering Models, and Novel Pathways Involving Non-Coding RNA - Kastner, Nina; Zlabinger, Katrin; Spannbauer, Andreas; Traxler, Denise; Mester-Tonczar, Julia; Hašimbegović, Ena; Gyöngyösi, Mariann (Frontiers in Pharmacology, 2020)
Cardiac hypertrophy is an ongoing clinical challenge, as risk factors such as obesity, smoking and increasing age become more widespread, which lead to an increasing prevalence of developing hypertrophy. Pathological hypertrophy is a maladaptive response to stress conditions, such as pressure overload, and involve a number of changes in cellular mechanisms, gene expression and pathway regulations. Although several important pathways involved in the remodeling and hypertrophy process have been identified, further research is needed to achieve a better understanding and explore new and better treatment options. More recently discovered pathways showed the involvement of several non-coding RNAs, including micro RNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), which either promote or inhibit the remodeling process and pose a possible target for novel therapy approaches. In vitro modeling serves as a vital tool for this further pathway analysis and treatment testing and has vastly improved over the recent years, providing a less costly and labor-intensive alternative to in vivo animal models.